The Level of Interest of Pangkalpinang Residents in The Bukit Pagoda Nusantara Tourist Destination in Sungailiat District, Bangka Regency - Cahya, Jodi; Daffa, Muhammad Rifqy; Syawana, Dhiyaa; Syahrani, Rizkita (Masyarakat Pariwisata : Journal of Community Services in Tourism, 2024)
Pagoda Nusantara Hill is one of the mainstay tourist destinations on Bangka Island. With its theme centered around Chinese culture, Pagoda Nusantara exudes its own unique charm. It can also attract local and foreign tourists. Pagoda Nusantara Hill also carries a religious theme. In addition to its status as a tourist destination, Pagoda Nusantara Hill also serves as a Buddhist place of worship. The natural beauty in the form of hills makes this tourist destination have its own tourist attraction. This study aims to analyze the level of interest that Pangkalpinang residents have in the Bukit Pagoda Nusantara tourist attraction, located in Sungailiat District, Bangka Regency. This research employs a quantitative and descriptive approach to assess the level of tourist interest in Bukit Pagoda Nusantara tourist destinations. The data is obtained based on the results of filling out a questionnaire using Google Forms.  The link from the Google form is distributed to Pangkalpinang residents who have visited the Bukit Pagoda Nusantara tourist destination via WhatsApp. The validity of the data obtained in the form of the author writing a caption on the Google form link in the form of “Only for Pangkalpinang residents who have visited Bukit Pagoda Nusantara.”.  Based on the results of the Google form, 37 respondents were obtained who filled in several questions that had been prepared by the author. The results obtained from this study state that the level of interest of Pangkalpinang residents in the Bukit Pagoda Nusantara tourist destination is 47% (low level).  Critics and suggestions for Bukit Pagoda Nusantara are that the most important thing is improving road access for visitors to make it easier to access the tourist attractions. In addition, it is hoped that the staff can maintain and repair facilities that are damaged or that are no longer suitable for use by visiting tourists. This will enhance the interest of tourists in visiting the area.